Impact of human sepsis on CCCTC-binding factor associated monocyte transcriptional response of Major Histocompatibility Complex II components - Siegler, Benedikt Hermann (PLoS One, 2018)
BACKGROUND: Antigen presentation on monocyte surface to T-cells by Major Histocompatibility Complex, Class II (MHC-II) molecules is fundamental for pathogen recognition and efficient host response. Accordingly, loss of Major Histocompatibility Complex, Class II, DR (HLA-DR) surface expression indicates impaired monocyte functionality in patients suffering from sepsis-induced immunosuppression. Besides the impact of Class II Major Histocompatibility Complex Transactivator (CIITA) on MHC-II gene expression, X box-like (XL) sequences have been proposed as further regulatory elements. These elements are bound by the DNA-binding protein CCCTC-Binding Factor (CTCF), a superordinate modulator of gene transcription. Here, we hypothesized a differential interaction of CTCF with the MHC-II locus contributing to an altered monocyte response in immunocompromised septic patients. METHODS: We collected blood from six patients diagnosed with sepsis and six healthy controls. Flow cytometric analysis was used to identify sepsis-induced immune suppression, while inflammatory cytokine levels in blood were determined via ELISA. Isolation of CD14(++) CD16(—)monocytes was followed by (i) RNA extraction for gene expression analysis and (ii) chromatin immunoprecipitation to assess the distribution of CTCF and chromatin modifications in selected MHC-II regions. RESULTS: Compared to healthy controls, CD14(++) CD16(—)monocytes from septic patients with immune suppression displayed an increased binding of CTCF within the MHC-II locus combined with decreased transcription of CIITA gene. In detail, enhanced CTCF enrichment was detected on the intergenic sequence XL9 separating two subregions coding for MHC-II genes. Depending on the relative localisation to XL9, gene expression of both regions was differentially affected in patients with sepsis. CONCLUSION: Our experiments demonstrate for the first time that differential CTCF binding at XL9 is accompanied by uncoupled MHC-II expression as well as transcriptional and epigenetic alterations of the MHC-II regulator CIITA in septic patients. Overall, our findings indicate a sepsis-induced enhancer blockade mediated by variation of CTCF at the intergenic sequence XL9 in altered monocytes during immunosuppression.